Basic Characteristics and Positioning of Multilayer Electrostatic Actuator Supported by Only Lubrication Oil - Md Ghazaly, Mariam (2011)
The present paper describes the characteristic switching of a multilayer thin electrostatic actuator supported by only lubricating oil and its application in the control of an ultra-precision fine stage.